1986
DOI: 10.1063/1.336473
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of space-charge injection from a needle electrode into dielectrics

Abstract: We show that space-charge injection from a needle into a dielectric can be determined with a resolution of 10−15 °C, by using guarded needle electrodes and a charge compensating bridge circuit. The technique is applied to epoxy resin samples. A well-defined homogeneous space-charge cloud formation is observed in quantitative agreement with a field-limiting space-charge concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(75 citation statements)
references
References 5 publications
6
62
1
6
Order By: Relevance
“…These and injection effects in bulk polymer were examined in detail, due to their relevance for electrical aging of extruded dielectric cables (Dang et al 1996). The concept of a critical field above which charge injection (Hibma and Zeller 1986) occurs is in agreement with the observation that below 1.6 × 10 7 V/m there is no charge injection in XLPE. PE has a dark nonohmic conductivity (Suh et al 1994) and it is electroluminescent under large electrical fields (Jonsson et al 1995), which is an evidence for the formation of chemical species in high-energy states trapped within the inert polyolefin; but these have not been identified or mapped.…”
Section: Electrostatic Phenomenasupporting
confidence: 83%
“…These and injection effects in bulk polymer were examined in detail, due to their relevance for electrical aging of extruded dielectric cables (Dang et al 1996). The concept of a critical field above which charge injection (Hibma and Zeller 1986) occurs is in agreement with the observation that below 1.6 × 10 7 V/m there is no charge injection in XLPE. PE has a dark nonohmic conductivity (Suh et al 1994) and it is electroluminescent under large electrical fields (Jonsson et al 1995), which is an evidence for the formation of chemical species in high-energy states trapped within the inert polyolefin; but these have not been identified or mapped.…”
Section: Electrostatic Phenomenasupporting
confidence: 83%
“…The underlying principle is that the volume of the encapsulant that is exposed to the highest fields is very small, and this reduces the risk of breakdown initiation. However, another possibility suggests itself: Perhaps the 828-Z epoxy has greater high-field conductivity [15] than the 459 epoxy, and the high fields in the near vicinity of sharp electrode features are able to relax on a time scale comparable to the voltage risetime. It is clear that elucidating the responsible physical process would require further research.…”
Section: F Discussionmentioning
confidence: 99%
“…The difference in dielectric strength is apparently caused by the different resin and/or curative. We speculate that a greater high-field conductivity [15] may be present in the older 828-Z formulation, which allows the high electric fields near electrode edges to relax on the time scale of the high-voltage pulse. Further experiments would be needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…considered that tree initiation can be regarded as partial electrical breakdown because of the permanent loss of dielectric insulating properties. And it is found that this partial destruction is due to the collision between electrons and polymer molecular chains [18,19]. When external electrical field was applied to the samples, the electrons in the bulk of PE films or injected from the needle electrode would be accelerated.…”
Section: Investigationsmentioning
confidence: 99%